PERILAKU MAKAN DAN STATUS GIZI REMAJA : STUDI KASUS SMAN 9 PAUH - Hafifatul Auliya Rahmy; Mutia Rahma; Idral Purnakarya; Mahdalena Mahdalena (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Background: Eating behavior is one of the factors that affect the nutritional status of adolescents. Adolescents are at risk of experiencing malnutrition, overnutrition, and micronutrient deficiencies. This study aims to describe adolescents' eating behavior and nutritional status at SMA Negeri 9 Pauh District. Method: The study was conducted at SMAN 9 Pauh District, Padang City. The population of this study was all students of SMAN 9 with a sample of 52 people who were selected using a simple random sampling method. The variables in this study were eating knowledge, eating attitudes, and body image, which was collected using a questionnaire and the act of eating variables using the SQ-FFQ. Determination of nutritional status is obtained from BMI/U. Result: A small proportion of adolescents experience overnutrition (25.0%), most of the knowledge of eating balanced nutrition for adolescents is low (82.7%), most of the attitudes of eating balanced nutrition for adolescents are positive (59.6%), most of the actions of eating nutrition-balanced adolescent is unbalanced (90.4%), most of the adolescent body image is positive (86.5%). Conclusion: A small proportion of adolescents experience overnutrition. Most of them have low knowledge of balanced nutrition, positive eating attitudes, unbalanced eating actions, and have a positive adolescent body image. For schools, it is necessary to cooperate with health workers in conducting health promotions regarding balanced nutrition guidelines, especially on the vegetable and fruit menu and body image. In addition, schools, teachers, and parents also need support in implementing balanced nutrition in children's diets.